A Decade of Learning Management System Research: A Bibliometric Analysis (2014–2023) - Darmawan, I Putu Ayub; Meisyani, Leiria (Universitas Veteran Bangun Nusantara, 2025)
This bibliometric analysis aims to explore the trends and developments in the literature concerning Learning Management Systems from 2014 to 2023. The analysis focuses on understanding how Learning Management System research has evolved and identifying key themes and gaps in the existing literature. The study employs a bibliometric approach, utilizing the Dimensions database to collect relevant literature published between 2014 and 2023. Key bibliometric indicators such as the number of publications, citation analysis, and co-authorship networks were analyzed to map the research landscape of the Learning Management System. The analysis reveals a significant increase in publications related to the Learning Management System, highlighting dominant themes such as technological integration, pedagogical effectiveness, and user experience. Key authors, institutions, and countries contributing to this field were identified, showcasing a collaborative network among researchers. The findings indicate a growing interest in Learning Management System research, emphasizing the need for further exploration of pedagogical strategies and technological advancements. This study underscores the importance of addressing existing gaps in the literature to enhance educational practices and outcomes through effective Learning Management System implementation. The Bibliometric Analysis of Learning Management Systems is beneficial to stakeholders in the education and research sectors. The findings of the study can help administrators and educators improve the implementation of pedagogical systems and strategies, as well as develop effective curricula. Researchers can also leverage these results to direct future studies and collaborations, as well as focus on under-researched areas or new trends, contributing to the advancement of knowledge in these areas.